PENGARUH HEALING ENVIRONMENT TERHADAP PEMULIHAN PASIEN ADIKSI NARKOBA DI SENTUL - Halim, Grady Fornathan; Sutisna, Sutarki (Jurusan Arsitektur dan Perencanaan, 2024)
The rehabilitation of drug addiction plays a vital role in aiding the recovery of patients addicted to narcotics, yet challenges persist in creating an environment conducive to well-being and recovery. The healing environment is recognized as a crucial factor in facilitating the physical, social, and psychological recovery process. This research aims to identify the influence of a healing environment on the well-being and recovery of drug addiction patients using a literature review approach. Relevant data was gathered from journals, books, theses, and internet sources. Data analysis was conducted to manage information that would serve as a guide in developing drug rehabilitation facilities prioritizing a holistic healing environment. The study demonstrates the importance of a healing environment in designing drug rehabilitation centers. Factors such as physical design, spatial arrangement, integration with nature, natural lighting, and social support are identified as key elements that enhance the well-being and recovery of drug addiction patients. With various natural facilities and green open spaces available, Sentul holds potential as an environment supportive of implementing the concept of a healing environment. Infrastructure that enables outdoor activities and engagement with nature can be crucial in facilitating the recovery process of drug addiction patients in that area. This research will result in a design concept for a drug rehabilitation center, constructing a physical atmosphere aligned with the needs of behavioral design. The design outcome will encompass the entirety of buildings, both indoor and outdoor spaces Keywords: drug addiction; healing environment; recovery; rehabilitation center Abstrak Rehabilitasi narkoba berperan vital dalam membantu pemulihan pasien adiksi narkotika, namun tantangan dalam menciptakan lingkungan yang mendukung kesejahteraan dan pemulihan masih ada. Lingkungan penyembuhan diakui sebagai faktor penting dalam memfasilitasi proses pemulihan secara fisik, sosial, dan psikologis. Penelitian ini bertujuan mengidentifikasi pengaruh healing environment terhadap kesejahteraan dan pemulihan pasien adiksi narkoba dengan menggunakan pendekatan studi literatur. Data relevan dikumpulkan dari jurnal, buku, skripsi, dan sumber internet. Analisis data dilakukan untuk mengelola informasi yang nantinya akan menjadi pedoman dalam pengembangan bangunan rehabilitasi narkoba yang mengutamakan lingkungan penyembuh secara holistik. Studi ini memperlihatkan pentingnya healing environment dalam merancang rehabilitasi narkoba. Faktor-faktor seperti desain fisik, pengaturan ruangan, integrasi dengan alam, pencahayaan alami, dan dukungan sosial diidentifikasi sebagai elemen kunci yang meningkatkan kesejahteraan dan pemulihan pada pasien adiksi narkoba. Dengan berbagai fasilitas alam dan ruang terbuka hijau yang ada, Sentul memiliki potensi sebagai lingkungan yang mendukung penerapan konsep healing environment. Infrastruktur yang memungkinkan aktivitas luar ruangan dan keterlibatan dengan alam dapat menjadi aspek penting dalam memfasilitasi proses pemulihan pasien adiksi narkoba di daerah tersebut. Dari penelitian ini akan dihasilkan sebuah konsep desain tempat rehabilitasi narkoba, dengan membangun suasana fisik yang menyesuaikan dengan kebutuhan perilaku perancangan ini. Hasil desain akan mencangkup bangunan, ruang luar dan dalam secara keseluruhan.